2008
DOI: 10.4102/pythagoras.v0i67.74
|View full text |Cite
|
Sign up to set email alerts
|

Mother tongue policies and mathematical terminology in the teaching of mathematics 

Abstract: The Department of Education in South Africa advocates collaborative and constructivist learning; however, observations indicate that little discussion occurs in most multilingual mathematics classes. In this paper we draw on a pilot study set in the Eastern Cape where teachers were introduced to the theory and practice of exploratory talk, and then tasked to perform an action research project on introducing discussion in their own multilingual mathematics classrooms. The results of the study suggest some succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
1
10
0
2
Order By: Relevance
“…Several reasons could be attributed to these disparities in learners' performances; one of them being that perhaps the learners had been used to mathematics tests written in English and that perhaps most Group B learners found the mathematics test written in Shona difficult to comprehend as the researcher had translated it using standard Shona which could be slightly different from the leaners' local Shona dialect. These observations corroborate Kazima (2008) who pointed out the difficulties associated with translating maths vocabulary (which is in English) into mother tongue, and also Mufanechiya and Mufanechiya (2011, p. 194) who found out that there were challenges faced by teachers and learners in the classrooms in their attempt to use mother tongue in the teaching and learning of mathematics at junior primary level. However, it would be worthwhile to carry out further research since in another study, Abubakar, Umar and Musawa (2015) found out that junior secondary school students who were taught mathematics in Hausa language performed better than their counterparts who were taught mathematics in English.…”
Section: Grade 5 Leaners' Test Resultssupporting
confidence: 80%
“…Several reasons could be attributed to these disparities in learners' performances; one of them being that perhaps the learners had been used to mathematics tests written in English and that perhaps most Group B learners found the mathematics test written in Shona difficult to comprehend as the researcher had translated it using standard Shona which could be slightly different from the leaners' local Shona dialect. These observations corroborate Kazima (2008) who pointed out the difficulties associated with translating maths vocabulary (which is in English) into mother tongue, and also Mufanechiya and Mufanechiya (2011, p. 194) who found out that there were challenges faced by teachers and learners in the classrooms in their attempt to use mother tongue in the teaching and learning of mathematics at junior primary level. However, it would be worthwhile to carry out further research since in another study, Abubakar, Umar and Musawa (2015) found out that junior secondary school students who were taught mathematics in Hausa language performed better than their counterparts who were taught mathematics in English.…”
Section: Grade 5 Leaners' Test Resultssupporting
confidence: 80%
“…In comparison, little similar research has been done on African 1 languages. Such research is particularly important in the many post-colonial countries, such as South Africa, where home language instruction has been implemented, at least in the early grades, but where the home languages do not have a long history of being used to teach mathematics (Kazima, 2008).…”
Section: Language and Mathematics Educationmentioning
confidence: 99%
“…Σειρά ερευνών (π.χ. Kazima, 2008;Setati & Barwell, 2008) επιβεβαιώνει ότι τα παιδιά που μαθαίνουν μαθηματικά σε μια δεύτερη γλώσσα, την οποία δεν κατέχουν επαρκώς, αντιμετωπίζουν πολύ περισσότερες δυσκολίες από τους γηγενείς συμμαθητές τους, κυρίως όταν το μαθηματικό περιεχόμενο παρουσιάζεται σε γλωσσικά πλαίσια, όπως για παράδειγμα τα λεκτικά προβλήματα (Adetula, 1990;Bernardo, 1999). Κατά τους Slavit και Ernst- Slavit (2007), στις τάξεις των μαθηματικών αλληλεπιδρούν και εναλλάσσονται διαφορετικοί τύποι γλωσσικών ποικιλιών.…”
Section: ο παράγοντας «γλώσσα»unclassified
“…Μια τέτοια πεποίθηση συνάδει με τα ευρήματα πολλών ερευνών (π.χ. Adetula, 1990;Bernardo, 1999;Kazima, 2008;Setati & Barwell, 2008 Η τελευταία παρατήρηση του Νίκου υποστηρίζεται και από τα ευρήματα ερευνών , καθώς οι αλλόγλωσσοι μαθητές που είναι επαρκείς τόσο στη γλώσσα που ομιλείται στο σπίτι όσο και στη γλώσσα διδασκαλίας, φαίνεται να αποδίδουν σημαντικά καλύτερα στα μαθηματικά από τους μονόγλωσσους μαθητές.…”
Section: σχεδιασμός και υλοποίηση της έρευναςunclassified